Enhancing handwashing skills in preschoolers through movement and puzzle games - Juni Sofiana; Dyah Puji Astuti; Rosmawati rosmawati (Community Empowerment, 2024)
Preschoolers are highly susceptible to illnesses due to their underdeveloped immune systems. The lack of understanding among preschoolers regarding the importance of proper hygiene practices makes them vulnerable to diseases such as respiratory infections, diarrhea, typhoid, and others. This community outreach initiative aimed to enhance preschoolers' knowledge and handwashing skills to prevent the spread of various diseases. The project employed educational sessions and hands-on training in handwashing techniques at TKIT Lukmanul Hakim. The outcomes demonstrated significant improvements: before the intervention, 18 children (54%) had adequate knowledge and 5 children (15.2%) had insufficient knowledge; after the intervention, 100% of the children exhibited good knowledge. Regarding handwashing skills, 20 children (60.6%) had poor skills before the training, while this improved to 69.7% with good skills after the training.